PENGARUH KEBIJAKAN DEVIDEN, PROFITABILITAS, STRUKTUR ASET DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - Merna Merna (Jurnal Akuntansi Bisnis, 2017)
This study aims to examine and analyze how the influence of dividend policy , profit , asset structure and growth of the company's debt policy . The data used is the consumer goods sector manufacturing companies listed in Indonesia Stock Exchange in 2014. There are 32 companies sampled and in accordance with the criteria . Testing this study using multiple regression and the results showed that the influence of corporate debt policy only asset structure . While the dividend policy , profitability , and growth company policy does not affect the company's debts . Keyword: debt policy , dividend policy , profitability , asset structure and growth of the company